Carl Priebe letter to W. Ross Silcock regarding Fremont County Snowy Owl sightings, November 24, 1993 - Priebe, Carlet al (1993)
Letter from Carl Priebe to W. Ross Silcock regarding Fremont County Snowy Owl sightings, November 24, 1993. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1993. Plustek - flatbed